Neuropathy and neuroarthropathy as a complication of diabetes and other diseases, with particular emphasis on painless fractures - a review of the literature - Michal Oleszko; Kamila Fularska; Aleksandra Kuźniar; Dominik Szawica; Edward Wąsiewicz; Radosław Bernacki; Piotr Bernacki; Martyna Dutka; Witold Zardzewiały (Journal of Education, Health and Sport, 2023)
Diabetes is now one of the most common chronic diseases. Its incidence is increasing, and thus the number of people suffering from its health complications is increasing. In 2015, 3 million people in Poland suffered from diabetes, and it is estimated that this number will increase to 4 million by 2040.